Perlindungan Hukum Terhadap Anak yang Menjadi Korban Tindak Pidana Penganiayaan Dalam Rumah Tangga di Wilayah Hukum Kepolisian Resor Kota Pekanbaru Berdasarkan Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga - TM Wawan Perdani; Dessy Artina; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Children are the next generation and successors to the development struggle as well as themandate and the gift of God Almighty, which we must always guard because in them the dignity, dignity andrights as human beings must be upheld. Legal protection for children is an effort and activity of all levels ofsociety in various positions and roles, who realize the importance of children for the nation and the nationin the future. If they are mature in their physical and mental and social growth, then they will replace theprevious generation.This research can be classified in the type of sociological legal research (empirical), which ismeant by sociological legal research (empirical) that is as a study that looks directly at the effect of theenactment of positive law on people's lives, because in this study the authors directly conduct research onlocation or place researched to provide a complete and clear description of the problem under study.Whereas viewed from the nature of the research reneline is descriptive, that is research that provides a clearand also detailed description of the problems examined by the author, namely Legal Protection AgainstChildren Who Become Victims of Torture in the Household in Pekanbaru Police Law Based on the LawNumber 23 of 2004 concerning the Elimination of Domestic Violence.From the results of the research the authors concluded, First, Protection of children in the LegalArea of the Pekanbaru City Police Resort is still not in line with expectations, because there are still manychildren who get violence and discrimination and violated children's rights while the protection that thegovernment should not provide well realized, secondly, the factors that cause obstruction of legal protectionfor children, are almost the same as law enforcement factors, which include the law, that in Law No. 23 of2004 not discussed in detail about how supervision of parents who commits a criminal act of abuse againsta child. law enforcers, that they did not regard the case as a criminal case, there was no further processregarding the perpetrators who escaped, the absence of a post mortem so there was a lack of evidence toprocess, and a lack of reports.Keywords: Legal Protection - Against Children - Victims of Torture in the Household.